Promoting the scholarship of teaching through reflective e-portfolios in teacher education - Pelliccione, Lina; Raison, Glenda (Routledge Taylor and Francis Group, 2009)
This study focuses on the goal of enhancing student reflection and learning with the key objective being to determine whether a structured reflective tool can enhance students’ ability to engage in a reflective cycle. A case study approach was adopted involving three cohorts of first year teacher education students in an Australian university over three years. The study found that the reflective tool assisted students to structure their reflections in a more cohesive manner, that without such a guide the majority of the students’ comments were descriptive and their reflective comment tended to be at a superficial level.